Yields of Bajra and Wheat With Saline Waters Applied Through Sprinkler and Surface Irrigation Methods - Aggarwal, M C; Singh, R; Verma, S K; Singh, Kanwar (Annals of Arid Zone, 2016)
Field experiments were conducted during kharif and rabi seasons of 1975 to 1978 at Haryana Agricultural University’s Research Farm, Hissar, to study the effectÂ£ of saline water applied through sprinkler and surface methods of irrigation on the performance of bajra and wheat crops and salt accumulation in soil. The results showed that saline water of 11.0 mmhosfcm EC by sprinkler reduced bajra: yield by 33 per cent whereas that of wheat by only 3 per cent. Saline water upto 6.0 mmhosfcm EC can be safe to bajra by sprinkler if applied in late evening or night hours. The marked reduction in bajra yield with application of 11.0 mmhosfcm EC water through sprinkler was mainly due to burning of leaves caused by excessive sodium content in water. This water did not cause damage to the same extent to wheat crop because of lower temperatures and high relative humidity prevailing in rabi season than in kharif season. In sprinkler irrigated plots, the salt accumulation in soil profile (0-120 cm) was 30-40 per cent less in comparison to surface irrigation. The study shows that the use of highly saline water with sprinkler can be better exploited for winter season wheat crop but its use for summer season crop like bajra is not feasible.